Evaluation of food suppliers by multi-channel buyers: Focusing on the moderating effect of distribution channel - Eunsoo Choi; Nayeong Kim; Junghoon Moon (Cogent Business & Management, 2024)
AbstractIn a multi-channel distribution environment, the selection and assessment of suppliers are pivotal to effective retailer performance management. This necessitates heightened qualifications and competence from suppliers. This study examines the relationship between the perception of supplier firms’ status, evaluation performance, and overall satisfaction of food buyers with suppliers in online/offline channels. In addition, this study investigates the moderating impacts of the distribution channel to explore the influence of the online/offline distribution channel on this relationship. For exploratory research, food buyers from 20 large retailers headquartered in Seoul, South Korea, were surveyed, and 110 valid questionnaires were used for analysis. Results of the study indicate that among suppliers’ firm factors, suppliers’ firm size and experience with the retailer were significantly and positively related to buyer satisfaction. Likewise, among evaluation factors, product competency and delivery reliability were significantly and positively related to buyer satisfaction. In addition, the results reveal that the distribution channel has moderating effects on the relationship between firm size and buyer satisfaction, as well as between experience with the retailer and buyer satisfaction. Therefore, the study verified that the distribution channel is an important factor that must be considered not only in the consumer market but also in the buying behavior research of the business-to-business market.